2023
DOI: 10.1088/1361-648x/ad1134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of magnetoimpedance behaviors in meander CoFeNiSiB amorphous ribbon for deformation sensing applications

Zhen Yang,
Mengyu Liu,
Liming Luo
et al.

Abstract: In this work, micro-ribbon strips and meanders based on CoFeNiSiB amorphous ribbons were fabricated by using the lithography technique and chemical etching. Flat and curved holders with different radius of curvature were obtained via 3D printing techniques for GMI testing. Longitudinal and transverse GMI (LGMI and TGMI) behaviors of micro-ribbon sensors in different bending directions and degrees were systematically investigated. The results show the LGMI and TGMI effects of micro-ribbon meanders with one turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The micron composite ribbon strips were obtained via designed mask and fabricated by MEMS technology including photolithography, wet etching, and magnetron sputtering. Detailed steps for the patterned single-layer ribbon strip have been reported elsewhere [8]. After finishing the patterned single-layer ribbon strip, the photoresist with a thickness of 1 µm was spin-coated on the surface of the ribbon strip.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The micron composite ribbon strips were obtained via designed mask and fabricated by MEMS technology including photolithography, wet etching, and magnetron sputtering. Detailed steps for the patterned single-layer ribbon strip have been reported elsewhere [8]. After finishing the patterned single-layer ribbon strip, the photoresist with a thickness of 1 µm was spin-coated on the surface of the ribbon strip.…”
Section: Methodsmentioning
confidence: 99%
“…Meander MI elements have become a focus of structural optimization research. Many theoretical and experimental studies on enhanced MI effects in ribbon meanders have been reported [6][7][8][9]. Laser cutting and wet etching are the main fabrication methods for micro-patterned ribbons [10,11].…”
Section: Introductionmentioning
confidence: 99%